Is School Function in Children with Down Syndrome the Same as Their Normally Developing Peers? A Preliminary Study - Farnoush Khosravi; minoo kalantari; Marzieh Pashmdarfard; Hamidreza Rostami; Alireza Akbarzadeh Baghban; Faezeh Heidari Beni (Journal of Rehabilitation Sciences and Research)
Background: Active participation in school is an effective way to foster children’s cognitive and social development. Children with Down syndrome (DS) face various challenges in the school environment due to different impairments in body functions and structures. Methods: In this cross-sectional study, a convenience sample of 51 children with DS was recruited from five schools for exceptional children, and their normally developing peers were recruited from four regular schools in Isfahan, Iran. Parents and teachers completed a demographic information questionnaire, and only teachers completed the School Function Assessment (SFA). Results: Children with DS had a moderate level of participation (criterion score = 60.04). Their school function scores were significantly lower than those of their normally developing peers. No significant relationship was found between gender, age, or educational level and school function scores in children with DS (p>0.05). Conclusion: The school functions of children with DS significantly differed from those of their normally developing peers. Children with DS performed significantly better in physical tasks than in cognitive-behavioral functions. The weakest cognitive-behavioral functions requiring particular rehabilitation interventions are task behavior/completion and safety.